2020
DOI: 10.1111/ppl.13149
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term somatic memory of salinity unveiled from physiological, biochemical and epigenetic responses in two contrasting rice genotypes

Abstract: Plants are constantly exposed to environmental fluctuations, that may occur in a single day or over longer periods. In many cases, abiotic stresses are transient and recurrent, impacting how plants respond in subsequent adverse conditions. Adaptation mechanisms may occur at the physiological, biochemical and molecular level, modifying transcriptional response, regulatory proteins, epigenetic marks or metabolites. Here, we aimed to uncover the different strategies that rice uses to respond to recurrent stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 90 publications
(102 reference statements)
0
29
0
Order By: Relevance
“…These modifications can lead to alterations in the way DNA is packaged and thus influence the accessibility of specific genes. In this study, do Amaral et al (2020) demonstrated that in the sensitive rice genotype, global levels of DNA methylation were only altered (significantly elevated) when the salt stress was administered at the reproductive stage, contrasting sharply with the tolerant genotype, which displayed huge variation in global DNA methylation across the different treatment time points and a strong relaxation of DNA methylation following the stress treatment (recovery). The researchers then looked at the correlation of these global methylation dynamics with the expression of key genes encoding proteins associated with DNA methylation and demethylation.…”
Section: Figmentioning
confidence: 54%
See 2 more Smart Citations
“…These modifications can lead to alterations in the way DNA is packaged and thus influence the accessibility of specific genes. In this study, do Amaral et al (2020) demonstrated that in the sensitive rice genotype, global levels of DNA methylation were only altered (significantly elevated) when the salt stress was administered at the reproductive stage, contrasting sharply with the tolerant genotype, which displayed huge variation in global DNA methylation across the different treatment time points and a strong relaxation of DNA methylation following the stress treatment (recovery). The researchers then looked at the correlation of these global methylation dynamics with the expression of key genes encoding proteins associated with DNA methylation and demethylation.…”
Section: Figmentioning
confidence: 54%
“…Despite this, research emerging from the field of plant science is continuing to reveal the sophisticated ways plants interact with their environments; discerning friend from foe, communicating information to neighbouring plants, and even recalibrating future stress responses based on the memories of past afflictions. In this issue of Physiologia Plantarum do Amaral et al ( 2020 ) investigated the mechanisms by which rice can recall exposure to an earlier stress event to better cope with future hardships; a phenomenon that resonates with the quote by poet W. S. Merwin: ‘What you remember saves you’.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…One example comes from studies showing that the long-term effects of cocaine and other drugs of abuse on neural plasticity involve alterations of histone modifications known to play a role in memory and learning [ 201 , 202 ]. Additional evidence comes from studies in plants in which transient changes in environmental salinity (hyperosmotic stress) result in changes in long-term somatic memory, which include epigenetic, transcriptional and physiological changes [ 203 , 204 ].…”
Section: Open Questions and Future Research Avenuesmentioning
confidence: 99%
“…The changes in expression of corresponding genes may have important consequences for the intercompartmental interactions in the stressed plant cells and result in the observed shifts in metabolism. There are several indications that salt stress affects DNA methylation and causes other epigenetic changes, including modifications of histones [22,23], in particular, depending on the salinity tolerance [24], and the level of methylation under salt stress can be mediated by phytohormones such as brassinosteroids [25]. The identified genes affected by methylation under NaCl treatment include those that participate in cell cycle, development, and different metabolic processes [26].…”
Section: Introductionmentioning
confidence: 99%